Evaluation of the contribution of herpes virus infection to the development and progression of chronic glomerular diseases in children - I.A. Kazyra; L.V. Rubanik; A.V. Sukala; T.K. Chebotareva (Zaslavsky O.Yu., 2018)
Background. Etiology of chronic glomerular diseases is not completely known to the present day. A number of factors, including viral infections, are described. Aim of the study: determination of antibodies to Epstein-Barr virus (EBV) (immunoglobulin (Ig) G to the nuclear and early antigen (AG), IgG and IgM to viral capsid AG), cytomegalovirus (CMV) (IgG, IgM), herpes simplex virus (HSV) (IgM, IgG), specific DNA fragments of herpes and polyomaviruses (BK and JC) in the blood serum and kidney tissue to clarify the role of viral infection in the development of glomerulopathies (GP) in children. Materials and methods. One hundred thirty children with primary and secondary GP were examined for the presence of antibodies and DNA fragments of herpes and polyomaviruses, including 42 recipients of the kidney transplant (Tx); 36 apparently healthy individuals were included in the control group. Ultrastructural analysis of kidney tissue for herpes viruses was performed. Results. IgM to HSV and IgM to CMV were detected in the sera of patients with secondary and primary GP more often than in controls (17.1 and 12.8 % vs. 0, 20 and 17 % vs. 5.5 %, respectively), and also children with Tx (vs. 0 % for HSV, 5 % for CMV, and 7 % for EBV, respectively). In 5 cases of secondary GP, IgM to 2 or more herpes viruses simultaneously were detected. In the blood serum of 24.4 % of children with secondary GP, both antibodies to EBV (IgG to early AG and IgM to viral capsid AG) and nucleic acids of HSV, CMV and EBV were detected. The ultrastructural analysis of 10 biopsy specimens showed the presence of type 1 and 2 HSV DNA in one case and CMV DNA in 2 cases. The features of the course of GP associated with herpetic infection are presented. Conclusions. Herpes viruses influence the development and course of the pathological process in chronic GP. The presented algorithm of virological examination of children with GP can be used in the practice of a nephrologist.